The composite face effect is robust against perceptual misfit - Kurbel, David (Atten Percept Psychophys, 2021)
The composite face effect—the failure of selective attention toward a target face half—is frequently used to study mechanisms of feature integration in faces. Here we studied how this effect depends on the perceptual fit between attended and unattended halves. We used composite faces that were rated by trained observers as either a seamless fit (i.e., close to a natural and homogeneous face) or as a deliberately bad quality of fit (i.e., unnatural, strongly segregated face halves). In addition, composites created by combining face halves randomly were tested. The composite face effect was measured as the alignment × congruency interaction (Gauthier and Bukach Cognition, 103, 322–330 2007), but also with alternative data analysis procedures (Rossion and Boremanse Journal of Vision, 8, 1–13 2008). We found strong but identical composite effects in all fit conditions. Fit quality neither increased the composite face effect nor was it attenuated by bad or random fit quality. The implications for a Gestalt account of holistic face processing are discussed.